The Influence Of Training, Employee Placement, And Compensation On The Work Performance Of PT. Employees. Astra International Honda, Tbk. Branch In Pinrang - Achmad, Abdurrahman (Jurnal Ekonomi, 2024)
The purpose of this research is to find out and analyze the influence of training on the work performance of PT employees. Astra International Honda, Tbk. Pinrang, to find out and analyze employee placement which influences the work performance of PT employees. Astra International Honda, Tbk. Pinrang, to find out and analyze the influence of compensation on the work performance of PT employees. Astra International Honda, Tbk. Pinrang, to find out and analyze which factors dominantly influence the work performance of PT employees. Astra International Honda, Tbk. Pinrang. This research uses a quantitative approach, and the respondents in this research are all employees of PT. Astra International Honda, Tbk. Branch in Pinrang. The conclusions of this research are 1). Training has a weak positive effect on the work performance of PT employees. Astra International Honda, Tbk. Pinrang Branch, 2). Employee placement has a weak positive effect on the work performance of PT employees. Astra International Honda, Tbk. Pinrang Branch, 3). Compensation has a strong positive effect on the work performance of PT employees. Astra International Honda, Tbk. Pinrang Branch, 4). It is compensation that has a dominant positive influence on the work performance of PT employees. Astra International Honda, Tbk. Pinrang Branch.